The Connection Of Entrepreneurship Characteristics And Business Performance Of Arabika Coffee Farmers - Elvin Desi Martauli (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
Entrepreneurship is a very important element in development, including in agriculture. One of the agriculture subjects that must have entrepreneurship characteristics to be able to encourage the improvement of farm performance is the farmer. The farmers in Tigapanah Sub-district, Karo District are farmers who are able to survive in performing coffee farming activities within various risks. The aim of this study was to analyze the cennection between entrepreneurship characteristics of Arabica coffee farmers in Tigapanah District to the farming performance. The method of sampling respondents was determined by the simple random sampling which involved 850 Arabica coffee farmers. The farmers in this study were 5% of the total respondents, which approximately 43 people. Based on the correlation analysis of Spearman Rank, on SPSS 20 was used to analyze the relationship between entrepreneurship characteristics to the farming performance. Based on the correlation analysis Spearman’s Rank, the results obtained that there was a positive and significant correlation between the characteristics of entrepreneurship with the performance of Arabica coffee farming. Positive and significant correlations were described by risk-taking, self-confident, task-and-outcome-oriented variables, leadership, future oriented and hard work towards the performance of Arabica coffee farming, which are market share, sales quantity, and income.